Implementação de elemento de colocação não nodal para análise tridimensional pelo método dos elementos de contorno - Ferreira, Walnório Graça (1990)
The present work aim is to study a non-nodal collocation procedure to consider discontinuities for Boundary Element Method analysis of three-dimensional elastic bodies. In the procedure developed, functional nodes remain on the corners, but collocation points are dislocated towards the interior of boundary elements. Triangular linear isoparametric boundary elements have been implemented in the computer cede developed. Polar coordinates were employed to perform singular integrals; integration with respect to r carried out analitically, and with respect to were e numerically by one-dimensional Gaussian quadrature. Regular integrations (including those which contained quasi-singular kernels) were computed numerically by employing selective two-dimensional Gaussian quadrature. ln the scheme employed, two successive coordena te transformations were carried out, the first maps the triangular domain into a rectangular one, and the second makes use of a third degree polynomial transformation, in order to improve accuracy. Finally the performance of the computer program developed is checked through the numerical analysis of three problems.